2009
DOI: 10.1002/iub.253
|View full text |Cite
|
Sign up to set email alerts
|

Metal ionophores – An emerging class of anticancer drugs

Abstract: SummaryCompounds that bind metals such as copper and zinc have many biological activities, including the ability to induce apoptosis in cancer cells. Although some of these compounds have been considered to act as chelators of metals, decreasing their bioavailability, others increase intracellular metal concentrations. We review recent work regarding the recognition of the biological effects of metal ionophores with different structures, particularly with regard to their actions upon cancer cells focusing on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
120
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(127 citation statements)
references
References 52 publications
4
120
0
Order By: Relevance
“…The choice of chelator is critical: on short time-scales (<1 hr), membrane-impermeable chelators deplete only extracellular copper and copper that may be rapidly moving through release-and-uptake cycles, while membrane-permeable chelators can access both intra-and extracellular copper, as well as potentially form ternary complexes with copper chaperones (15), preventing copper trafficking or mobilization. Additionally, copper ionophores, such as clioquinol and other 8-hydroxyquinoline (8HQ) derivatives, redistribute copper across cell and organelle membranes, altering the labile copper pool without adding or removing copper from the system (16,17). Changes to the labile copper pool may be assessed by the use of fluorescent small-molecule indicators that can equilibrate with kinetically accessible copper in the cytosol, enabling one to distinuguish labile copper from total copper, the latter of which is typically measured using direct techniques including X-ray fluorescence microscopy (XFM) or mass spectrometry imaging (14,18).…”
Section: Acquisition and Trafficking Of Copper In Mammalsmentioning
confidence: 99%
“…The choice of chelator is critical: on short time-scales (<1 hr), membrane-impermeable chelators deplete only extracellular copper and copper that may be rapidly moving through release-and-uptake cycles, while membrane-permeable chelators can access both intra-and extracellular copper, as well as potentially form ternary complexes with copper chaperones (15), preventing copper trafficking or mobilization. Additionally, copper ionophores, such as clioquinol and other 8-hydroxyquinoline (8HQ) derivatives, redistribute copper across cell and organelle membranes, altering the labile copper pool without adding or removing copper from the system (16,17). Changes to the labile copper pool may be assessed by the use of fluorescent small-molecule indicators that can equilibrate with kinetically accessible copper in the cytosol, enabling one to distinuguish labile copper from total copper, the latter of which is typically measured using direct techniques including X-ray fluorescence microscopy (XFM) or mass spectrometry imaging (14,18).…”
Section: Acquisition and Trafficking Of Copper In Mammalsmentioning
confidence: 99%
“…TPEN is usually used to generate the depleted sample for the determination of the autofluorescence, and zinc is used in combination with pyrithione to measure the maximum fluorescence [16]. Pyrithione is an ionophore that transports zinc, copper and lead across biological membranes [42]. Given in combination with zinc, it is able to induce apoptosis by facilitated intracellular zinc uptake, resulting in toxic intracellular zinc concentrations [43].…”
Section: Measurement Of Free Zn 2+mentioning
confidence: 99%
“…We previously reported that clioquinol acts as a zinc ionophore in Raji [18], DU-145 [19], and MCF-7 cells [26]. Treatment with zinc alone did not increase intracellular zinc levels in MCF-7 cells [26].…”
Section: Clioquinol Plus Zncl 2 But Not Cucl 2 Enhances P-body Assemblymentioning
confidence: 99%